2022
DOI: 10.1186/s12871-022-01622-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-time ultrasound-guided stellate ganglion block for migraine: an observational study

Abstract: Objective To observe whether ultrasound-guided stellate ganglion block (SGB) can effectively relieve migraine pain and improve the quality of migraine patients’ life. Methods 81 patients with migraines were enrolled in this study. The patients received SGB with 6 ml of 0.15% ropivacaine once every week for four times. Migraine was assessed with the Migraine Disability Assessment Scale (MIDAS) at baseline and three-months follow-up (Tm). The numeric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 38 publications
4
12
0
Order By: Relevance
“…The authors found that PNBs might be a safe and effective alternative headache management strategy for elderly patients with migraine, with an effectiveness rate of 81% for chronic migraine and 75% for episodic migraine, and no AEs associated with PNBs were reported 7 . A few studies have confirmed that SGB is effective in the treatment of migraine in young adults 13,14 . In the present study, we found that SGB treatment resulted in significant reduction in pain intensity in elderly patients with migraine.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The authors found that PNBs might be a safe and effective alternative headache management strategy for elderly patients with migraine, with an effectiveness rate of 81% for chronic migraine and 75% for episodic migraine, and no AEs associated with PNBs were reported 7 . A few studies have confirmed that SGB is effective in the treatment of migraine in young adults 13,14 . In the present study, we found that SGB treatment resulted in significant reduction in pain intensity in elderly patients with migraine.…”
Section: Discussionsupporting
confidence: 61%
“…Moon et al 13 reported a 63% and a 57% reduction in pain intensity in two young adults with bilateral migraine after 4 months of SGB procedures. Hou et al 14 also found that patients aged 8–62 years with unilateral migraine achieved up to a 71% reduction in pain intensity after 3 months of SGB treatment, from a mean (SD) NRS score of 7.0 (2.0) at baseline to 2.0 (2.0). The degree of reduction in pain intensity obtained with SGB treatment in our study was comparable to that achieved with SGB in younger patients with bilateral migraine and slightly less than that in younger patients with unilateral migraine.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although the mechanism of pain remains unclear, the application of SGB in the treatment of various types of pain remains feasible. Studies have revealed that the application of SGB to alleviate most of the symptoms of migraine in the treatment of migraine[ 11 , 12 ] and cluster headache[ 13 ] may be attributed to the inhibition of sympathetic overactivity or weakening of vascular inflammatory response. Furthermore, a previous study reported that ultrasound-guided SGB can effectively relieve cervical headache[ 14 ].…”
Section: Introductionmentioning
confidence: 99%